Geochemical characteristics of REY, Li, Ga trace elements in the No. 9 coal seam of the Daheng mine, Ningwu coalfield, Shanxi Province, China - Jin-xi Wang; Zhi-heng Fu; Ya-fan Hu; Zhen Yang; Jia-liang Ma; Yu-zhuang Sun (China Geology, 2021)
To understand the geochemical characteristics of the No.9 coal in the Daheng Mine of the Ningwu coalfield, the trace element analysis was conducted through X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma mass spectrometry (ICP-MS). The sedimentary environment was discussed according to the element geochemical parameters. The results show that Li, Ga, Hf, Zr, Nb, Th, and Ta are slightly enriched in the No. 9 coal of Daheng Mine. The average value of the rare earth elements and yttrium (∑REY) in coal here is 144.20 μg/g (excluding parting), which is higher than the average value of ∑REY in the world ’s coal and China ’s coal. The light rare earth elements (LREY) are enriched. The content of Eu was 0.12–2.10 μg/g with an average of 0.57 μg/g, and the Eu is obviously negatively abnormal. Most of the trace elements in the coal are positively correlated with the ash content, which shows that the occurrence of these trace elements is related to inorganic minerals. The results of sequential chemical extraction experiments show that rare earth elements mainly exist in coal in the form of aluminosilicate. The value of the Sr/Ba and the content of S reflect that the coal-forming environment was influenced by seawater. The values of V/Cr and Ni/Co reflect that the peat swamp is in an anaerobic environment and a strongly reducing environment during the coal-forming period.